Contribution of Electrocardiographic Accelerated Ventricular Rhythm Alarms to Alarm Fatigue - Suba, Sukardi (Am J Crit Care, 2019)
BACKGROUND: Excessive electrocardiographic alarms contribute to “alarm fatigue,” which can lead to patient harm. In a prior study, one-third of audible electrocardiographic alarms were for accelerated ventricular rhythm (AVR), and most of these alarms were false. It is uncertain whether true AVR alarms are clinically relevant. OBJECTIVES: To determine from bedside electrocardiographic monitoring data (1) how often true AVR alarms are acknowledged by clinicians, (2) whether such alarms are actionable, and (3) whether such alarms are associated with adverse outcomes (“code blue,” death). METHODS: Secondary analysis using data from a study conducted in an academic medical center involving 5 adult intensive care units with 77 beds. Electronic health records of 23 patients with 223 true alarms for AVR were examined. RESULTS: The mean age of the patients was 62.9 years, and 61% were white and male. All 223 of the true alarms were configured at the warning level (ie, 2 continuous beeps), and 215 (96.4%) lasted less than 30 seconds. Only 1 alarm was acknowledged in the electronic health record. None of the alarms were clinically actionable or led to a code blue or death. CONCLUSIONS: True AVR alarms may contribute to alarm fatigue. Hospitals should reevaluate the need for close monitoring of AVR and consider configuring this alarm to an inaudible message setting to reduce the risk of patient harm due to alarm fatigue. Prospective studies involving larger patient samples and varied monitors are warranted.